Nonresponders, Partial Responders, and Complete Responders to PDE5 Inhibitors Therapy According to IIEF Criteria: Validation of an Anchor‐Based Treatment Responder Classification. (11th October 2013) - Yang, May; Ni, Xiao; Sontag, Angelina; Litman, Heather J.; Rosen, Raymond C.
Abstract Introduction Despite widespread use of the International Index of Erectile Function (IIEF) in erectile dysfunction (ED) research, there are no published criteria for classifying ED treatment responders in clinical trials or patient management settings. A new classification for treatment response in men with ED has been developed and validated in a large clinical trial database. Aim The study aims to test discriminant and convergent validity of the responder classification and examine the role of covariates. Method Treatment assignment was used to test discriminant validity. The diary‐based Sexual Encounter Profile (SEP) question ("Did your erection last long enough for you to have successful intercourse?") and Global Assessment Question (GAQ) ("Has the treatment you have been taking over the past study interval improved your erections?") were used to evaluate convergent validity. Chi‐square and Cochran–Armitage trend tests were used to examine outcome associations. Logistic regression was used to further assess the relationship of outcomes controlling for covariates. Main Outcome Measure The classification measure was developed and validated in a database from 17 clinical trials in 3, 252 men with ED randomized to placebo or tadalafil. The treatment responder is defined as complete (erectile function [EF] ≥ 26); partial (EF < 26; met minimal clinically important difference [MCID] criteria); or nonresponder following treatment (EF < 26; did not meet MCID). Results The new responder definition performed consistently well in all prespecified tests of validity. Eighty‐nine percent of subjects classified as complete responders were in the treatment group, and the responder definition was associated with changes on the SEP and GAQ measures, respectively (SEP odds ratio [OR] = 14, 95% confidence intervals [CI] 11–17; GAQ OR = 50, 95% CI 39–88; complete vs. nonresponders). Conclusions We developed and validated a novel method of defining an ED treatment responder based on multiple IIEF criteria and using other measures (SEP, GAQ) for validation. The results have implications for understanding results of clinical trials in ED, and in monitoring response to treatment in the clinic. Yang M, Ni X, Sontag A, Litman HJ, and Rosen RC. Nonresponders, partial responders, and complete responders to PDE5 inhibitors therapy according to IIEF criteria: Validation of an anchor‐based treatment responder classification. J Sex Med 2013;10:3029–3037.